2005
DOI: 10.1088/0967-3334/27/2/003
|View full text |Cite
|
Sign up to set email alerts
|

Development of a quantitative assessment system for correlation analysis of footprint parameters to postural control in children

Abstract: It is known that neurological impairments impact postural stability, but few studies have observed the biomechanical influence of foot structure on balance. The aim of this study was to develop an integrated device for investigating the relationship between static balance and the foot structure, derived from a footprint image, under clinical tests of sensory interactions. Quantitative analysis of the footprint image acquired during balanced standing was developed as an indirect measure of the longitudinal arch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
24
1
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 28 publications
3
24
1
3
Order By: Relevance
“…Whilst controversy regarding the effect of foot posture on balance measures has previously been demonstrated, [1,2,6] our findings revealed that the prone feet have increased sway velocity of COG in the US-EC condition. In one of the three studies, [6] a balance test with compliant surface resulted in increased COG sway velocity in young children with feet with less plantar contact to the supporting surface.…”
Section: Discussioncontrasting
confidence: 41%
See 2 more Smart Citations
“…Whilst controversy regarding the effect of foot posture on balance measures has previously been demonstrated, [1,2,6] our findings revealed that the prone feet have increased sway velocity of COG in the US-EC condition. In one of the three studies, [6] a balance test with compliant surface resulted in increased COG sway velocity in young children with feet with less plantar contact to the supporting surface.…”
Section: Discussioncontrasting
confidence: 41%
“…In one of the three studies, [6] a balance test with compliant surface resulted in increased COG sway velocity in young children with feet with less plantar contact to the supporting surface. A second study has also suggested that feet with less plantar contact area have larger COG sway because of absence of medial block, or less plantar cutaneous sensory information.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bone sequences are known to play an important role in postural control and walking (22). The hallux and the first metatarsophalangeal joint play major roles in walking; in the presence of severe hallux valgus, the walking patterns of elderly people may change.…”
Section: Discussionmentioning
confidence: 99%
“…Se compararmos as técnicas diretas de medidas antropométricas dos pés para mensurar a altura do arco longitudinal medial, a radiografia dos pés e o método indireto da imagem da impressão plantar, o último apresenta vantagens por prover informações sobre o arco plantar e suas anormalidade, por apresentar baixo custo e ser facilmente disponível e livre de radiação (16) . Devido ao crescimento, na infância há uma larga variação das dimensões e formas dos pés, o que dificulta estabelecer os limites de normalidade do arco plantar nas crianças (5) .…”
Section: Discussionunclassified